1990
DOI: 10.1530/jrf.0.0880383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of melatonin implants on reproduction in the male silver fox (Vulpes vulpes)

Abstract: In June 1987, when the testes were fully regressed, 5 males were given s.c. implants of 40 mg melatonin. The same treatment was repeated in August and October 1987. Five males served as controls. Plasma concentrations of melatonin increased significantly in treated males and were still elevated at the end of the study in April 1988. The changes in testicular volume and blood plasma concentrations of testosterone in response to GnRH indicated that melatonin administration promoted testicular development. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The effects of constant exposure to high melatonin concentrations on the reproductive cycle result in an initial period of rapid testicular growth followed by involution (Forsberg et al, 1990), in the present study registered as a time shift in peak testosterone secretion.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The effects of constant exposure to high melatonin concentrations on the reproductive cycle result in an initial period of rapid testicular growth followed by involution (Forsberg et al, 1990), in the present study registered as a time shift in peak testosterone secretion.…”
Section: Discussionsupporting
confidence: 58%
“…Earlier experiments have shown that the reproductive cycle as well as the moulting cycle of the silver fox (Vulpes vulpes) male can be influenced by changes in photoperiod (Forsberg et al, 1989) and melatonin administration (Connor, 1988;Forsberg et al, 1990). Under natural daylight con¬ ditions plasma concentrations of testosterone and thyroxine show distinct seasonal variations (Joffre & Joffre, 1975;Joffre, 1976;Maurel & Boissin, 1981), and prolactin secretion increases during and after the mating season (Maurel et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…However, a long latency for the responses of the Downloaded by [University of Saskatchewan Library] at 14:04 27 December 2014 gonadal system has already been reported in mink, either following ganglionectomy (Maurel et al, 1992a), or in intact animals during the seasonal cycle of reproduction (Jallageas et al, 1994a). The occurrence of a refractory state following long-term effects of melatonin administration has also been described in other species: a decrease in testicular activity was observed in the ram and in the fox (Lincoln and Ebling, 1985;Forsberg et al, 1990), while oestrus cycles were abolished in the ewe (Nowak and Rodway, 1985).…”
Section: Discussionmentioning
confidence: 91%
“…), and silver fox ( Vulpes vulpes ) (Forsberg et al. ). However, further research is required to develop a better understanding of the impact of changes in latitude on melatonin secretion and the potential benefits of therapeutic melatonin administration to captive breeding programs that are not sustainable.…”
Section: Expanding Evolutionary Perspectives In Zoo Population Managementioning
confidence: 99%
“…Monitoring and supplementing melatonin levels may be a possible method for animal managers to regulate circadian and seasonal rhythms of translocated species to enhance reproduction and welfare. Melatonin implants have been used to regulate reproductive performance in sheep (Ovis aries) (Hanif and Williams 1991;O'Callaghan et al 1991;Haresign 1992), deer (Dama dama) (Asher et al 1988), and silver fox (Vulpes vulpes) (Forsberg et al 1990). However, further research is required to develop a better understanding of the impact of changes in latitude on melatonin secretion and the potential benefits of therapeutic melatonin administration to captive breeding programs that are not sustainable.…”
Section: Melatonin Photoperiod and Changes In Latitudementioning
confidence: 99%